Efficacy of adding midazolam to paracetamol in pain control of patients with a primary headache: A randomized, clinical trial study - Mahin Amini-Parikhani; Amir Ghaffarazad; Hassan Soleimanpour; Haniyeh Ebrahimi-Bakhtavar; Farzad Rahmani (Turkish Journal of Emergency Medicine, 2020)
OBJECTIVES: This study aimed to determine the effect of adding intravenous midazolam to paracetamol in the treatment of patients with primary headache referring to the emergency department. METHODS: In a randomized clinical trial, 120 patients (18–65 years old) with primary headache referring to the emergency department were enrolled. Patients were divided into two groups (case: paracetamol + midazolam and control: paracetamol + placebo), and the treatment was administered based on the treatment group. The severity of pain (according to the initial Visual Analog Scale) and at different times after the treatment onset (15, 30, and 60 min) and the degree of satisfaction with the treatment were compared in two groups of patients. RESULTS: There were no statistically difference between the two groups about the median of pain severity at the time of 0 min (case: 8 vs. control: 8), 15 min (case: 6 vs. control: 6), and 30 min (case: 4 vs. control: 4) with P > 0.05. Headache severity at 60 min after the treatment onset in the case group (median: 1) was less than that of the control group (median: 3). There was also a statistically significant difference in the median of patient satisfaction in the case group (case: 9 and control: 7 with P < 0.001) and satisfaction in the case group was higher. CONCLUSIONS: Based on our primary and secondary outcomes and the results of the study, we conclude that adding intravenous midazolam to paracetamol do not improve the therapeutic response ratio over time, but the effect of this intervention appeared after 1 h.